Jejunal adenocarcinoma after biliopancreatic diversion. Report of a case. Issue 3 (May 2022) - Cossu, Maria L.; Fancellu, Alessandro; Feo, Claudio F.; Ginesu, Giorgio C.; Sogos, Sebastiano; Ariu, Maria L.; Porcu, Alberto
Abstract: The effects of bariatric surgery on the development of gastrointestinal cancers remain ill defined. We present a case of jejunal adenocarcinoma developing 19 years after biliopancreatic diversion (BPD) procedure according to Scopinaro's technique. The patient developed a marked distension of the biliopancreatic limb caused by a jejunal mass, evolving towards the so called "duodenal blowout". Emergency jejunal resection of the biliopancreatic limb, with creation of a new end-to-side jejunal-ileal anastomosis was necessary. The histological examination resulted in a moderately-differentiated ulcerated adenocarcinoma, with reactive lymph nodes and tumor-free resection margins. Tumors of the gastrointestinal system can arise following malabsorptive operations for morbid obesity, and they may be difficult to diagnose, since the symptoms are often attributed to the anatomical-functional changes resulting from this type of surgery. The case reported herein suggests that there is a need for surveillance in patients complaining of digestive symptoms after malabsorptive bariatric surgery.